Perceptions of University Students towards Digital Transformation during the Pandemic - Carlos Hervás-Gómez; María Dolores Díaz-Noguera; Ana María De la Calle-Cabrera; Olga Guijarro-Cordobés (MDPI AG, 2021)
The aim of this study is to determine the perceptions of university students toward teaching-learning processes during the COVID-19 pandemic. This research gathers inquiries made worldwide on the perceptions of students in higher education during a state of alarm. The proposed objectives were (a) to analyse the perception of students toward teaching-learning processes in university; (b) to determine the assessment given by students about the changes that took place in university teaching as a result of COVID-19; and (c) to explore resources (hardware and software), professional collaboration, digital pedagogy and student empowerment (motivation) regarding digital education and recent changes in university teaching due to the pandemic. This study used a non-experimental, descriptive design based on opinion polls or surveys. The results show a positive correlation between digital pedagogy, student motivation and digital environments. As a conclusion, we encourage the scientific community to continue delving into the motivation, collaboration and reflective exchange of experiences, self-learning and promotion of initiatives that foster the development of competencies in future teachers. It is also important to continue the research on integrated designs in training processes in university, tutoring and continuous evaluation, as they are key for digital transformation in universities.